Alterations in adenosine metabolism and signaling in patients with chronic obstructive pulmonary disease and idiopathic pulmonary fibrosis. - Yang Zhou (PLoS ONE, 2010)
BACKGROUND:Adenosine is generated in response to cellular stress and damage and is elevated in the lungs of patients with chronic lung disease. Adenosine signaling through its cell surface receptors serves as an amplifier of chronic lung disorders, suggesting adenosine-based therapeutics may be beneficial in the treatment of lung diseases such as chronic obstructive pulmonary disease (COPD) and idiopathic pulmonary fibrosis (IPF). Previous studies in mouse models of chronic lung disease demonstrate that the key components of adenosine metabolism and signaling are altered. Changes include an up-regulation of CD73, the major enzyme of adenosine production and down-regulation of adenosine deaminase (ADA), the major enzyme for adenosine metabolism. In addition, adenosine receptors are elevated. METHODOLOGY/PRINCIPAL FINDINGS:The focus of this study was to utilize tissues from patients with COPD or IPF to examine whether changes in purinergic metabolism and signaling occur in human disease. Results demonstrate that the levels of CD73 and A(2B)R are elevated in surgical lung biopsies from severe COPD and IPF patients. Immunolocalization assays revealed abundant expression of CD73 and the A(2B)R in alternatively activated macrophages in both COPD and IPF samples. In addition, mediators that are regulated by the A(2B)R, such as IL-6, IL-8 and osteopontin were elevated in these samples and activation of the A(2B)R on cells isolated from the airways of COPD and IPF patients was shown to directly induce the production of these mediators. CONCLUSIONS/SIGNIFICANCE:These findings suggest that components of adenosine metabolism and signaling are altered in a manner that promotes adenosine production and signaling in the lungs of patients with COPD and IPF, and provide proof of concept information that these disorders may benefit from adenosine-based therapeutics. Furthermore, this study provides the first evidence that A(2B)R signaling can promote the production of inflammatory and fibrotic mediators in patients with these disorders.